سیرت نگاری میں عزۃ دروزہ کا منہج ( سیرۃ الرسول صور مقتبسۃ من القرآن الکریم کا تحقیقی و تحلیلی مطالعہ): The Method Of Izzat Darwazah In The SI ̅Rah Writing (An Analytical And Investigative Study Of SI ̅Rat-Al-Rasul SU ̅War MuqtA ̅Bisah Min Al Qur’an Al-Karim) - Dr. Asifa Aslam (Al-Amīr Research Journal for Islamic Studies, 2025)
When the Jews and Christians established their religious, political, scientific and literary superiority over the Muslim nations, they considered it necessary to crush the Muslims not only political but also scientifically and culturally in order to maintain their dominance so that they could never come up against them. For this purpose, the resorted many political, educational, social, cultural and literary movements. One of them is an Orientalist Movement which was trying to eradicate the Muslims from the beginning of Islam. During this colonial period, the Orientalist Movement accelerated its activities and adopted various methods to alienate the Muslims from Islamic sciences and the S rah of Prophet Muhammad. On the one hand, The Orientalists claimed to impartial and publicity the good character and ethics of Holy Prophet, But on the other hand, in the guise of research, they began to poison in the minds of Muslims and wrote such literature about the Prophet Muhammad that raised doubts and suspicious in the minds of Muslims. To respond to slander of these people, Many S rah writers adopted various methods. One of them is to present the S rah of Prophet by extracting the details from Qur’an. This research paper aims to present the analytical study of “S rat-al-Rasul Suwar Muqtabisah min al-Qur’an al-Karim” of famous S rah writer Izzat Darwazah who attempted to portray the life of Prophet Muhammad by extracting details from Qur’an. An analytical and investigative study of book concludes that all the aspects of the life of Holy Prophet has been illustrated as recorded in the Qur’an and the author gained his goals through the application of his method.